2009
DOI: 10.1111/j.1439-0418.2009.01387.x
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting migration of cereal aphids (Hemiptera: Aphididae) in autumn and spring

Abstract: The migration of cereal aphids and the time of their arrival on winter cereal crops in autumn and spring are of particular importance for plant disease (e.g. barley yellow dwarf virus infection) and related yield losses. In order to identify days with migration potentials in autumn and spring, suction trap data from 29 and 45 case studies (locations and years), respectively, were set-off against meteorological parameters, focusing on the early immigration periods in autumn (22 September to 1 November) and spri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 77 publications
(145 reference statements)
0
36
0
Order By: Relevance
“…Mean temperature provides an indication of the thermal environment to which insects are exposed and, conceivably, influence their developmental rate and behaviour (Beck 1983;Klueken et al 2009 experienced at the Tzaneen and Sabie monitoring trial sites during the hot summer and early autumn months, sometimes for up to 6 hours a day, could possibly explain the decrease in the number of T. peregrinus individuals encountered during the hot summer months.…”
Section: Monitoring Trialmentioning
confidence: 99%
“…Mean temperature provides an indication of the thermal environment to which insects are exposed and, conceivably, influence their developmental rate and behaviour (Beck 1983;Klueken et al 2009 experienced at the Tzaneen and Sabie monitoring trial sites during the hot summer and early autumn months, sometimes for up to 6 hours a day, could possibly explain the decrease in the number of T. peregrinus individuals encountered during the hot summer months.…”
Section: Monitoring Trialmentioning
confidence: 99%
“…such as that by Klueken et al (2009), have shown the possibility of forecasting the migration of pest insects using several exogenous predictor variables. Migration mechanisms are highly elaborate, and proximate factors in migration are both exogenous (environmental cues that can trigger or inhibit migrations) and endogenous (under physiological and hormonal control).…”
Section: Introductionmentioning
confidence: 99%
“…Several authors (Chattopadhyay et al, 2005;Zamani et al, 2006;Klueken et al, 2009) have predicted aphid occurrence by meteorological factors.…”
Section: Introductionmentioning
confidence: 99%